Inclusive Health and First-Aid Education Assistance through Traditional Games as an Implementation of Local Wisdom for Children with Special Needs - Eko Retno Mulyaningrum; Rivanna Citraning Rachmawati; Wijayanto Wijayanto; Arif Wibisono (Yayasan Keluarga Guru Mandiri, 2026)
Children with special needs are more vulnerable to minor injuries due to limited motor coordination and low awareness of environmental risks, emphasizing the need for accessible first-aid education. This community service program aimed to improve inclusive health literacy and basic first-aid skills by integrating traditional games, Bola Bekel and Ular Naga, as culturally based learning media. A Participatory Action Research (PAR) approach was applied in collaboration with teachers and students at Widya Bhakti Special Needs School, Semarang, through planning, implementation, and evaluation stages. The adapted games introduced essential first-aid concepts, including recognizing common injuries, selecting appropriate first-aid equipment, and practicing simple response procedures through guided simulations. The program results showed increased student understanding of first-aid tools, greater confidence in performing basic first-aid actions, improved motor coordination, and enhanced social interaction. In addition, the activity strengthened partner empowerment by improving teachers’ capacity to independently implement game-based first-aid learning and integrate it into school activities, supporting program sustainability. This program contributes to the development of culturally relevant, inclusive, and sustainable first-aid education models for children with diverse abilities.